2013
DOI: 10.1128/mcb.00116-13
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Copper Response Is Regulated by DNA Damage

Abstract: Copper is an essential but potentially toxic redox-active metal, so the levels and distribution of this metal are carefully regulated to ensure that it binds to the correct proteins. Previous studies of copper-dependent transcription in the yeast Saccharomyces cerevisiae have focused on the response of genes to changes in the exogenous levels of copper. We now report that yeast copper genes are regulated in response to the DNA-damaging agents methyl methanesulfonate (MMS) and hydroxyurea by a mechanism(s) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 68 publications
(74 reference statements)
1
17
0
Order By: Relevance
“…Indeed, assuming a conserved role of KIN17, one could hypothesize that Cu is required to face conditions impairing DNA replication and genome integrity. Interestingly, a recent study provided evidence in favor of the activation of the Cu-import system in Saccharomyces cerevisiae in response to treatments with DNA-damaging agents (Dong et al, 2013). In this regard, our data supporting the KIN17-SPL7 interaction would reinforce the requirement of Cu in DNA metabolism and provide a first indication of how this coupling is achieved in plants.…”
Section: Discussionsupporting
confidence: 71%
“…Indeed, assuming a conserved role of KIN17, one could hypothesize that Cu is required to face conditions impairing DNA replication and genome integrity. Interestingly, a recent study provided evidence in favor of the activation of the Cu-import system in Saccharomyces cerevisiae in response to treatments with DNA-damaging agents (Dong et al, 2013). In this regard, our data supporting the KIN17-SPL7 interaction would reinforce the requirement of Cu in DNA metabolism and provide a first indication of how this coupling is achieved in plants.…”
Section: Discussionsupporting
confidence: 71%
“…Copper binding to this domain promotes an interaction between the transactivation domain and DNA binding domain, which in turn prevents Mac1 from binding to DNA and activating gene expression [55]. While this copper-induced allosteric switch explains how Mac1 activity can be regulated by copper, new studies have revealed that activation of gene expression under copper-limiting conditions requires a functional Cu-Zn superoxide dismutase (Sod1), and that Mac1 activity can be affected by the DNA damaging agent MMS [56, 57]. MMS is thought to trigger changes in the redox status of the regulatory cysteine residues within Mac1, which in turn correlates with alterations in Mac1 activity [57].…”
Section: Transcriptional Control Of Metal-homeostasismentioning
confidence: 99%
“…While this copper-induced allosteric switch explains how Mac1 activity can be regulated by copper, new studies have revealed that activation of gene expression under copper-limiting conditions requires a functional Cu-Zn superoxide dismutase (Sod1), and that Mac1 activity can be affected by the DNA damaging agent MMS [56, 57]. MMS is thought to trigger changes in the redox status of the regulatory cysteine residues within Mac1, which in turn correlates with alterations in Mac1 activity [57]. These newer studies suggest that other environmental factors alter, or may be critical to, copper sensing.…”
Section: Transcriptional Control Of Metal-homeostasismentioning
confidence: 99%
“…Most knowledge of the intricacies of Cu-mediated metal detoxification is obtained from observations in the yeast Saccharomyces cerevisiae. Under conditions of high Cu, S. cerevisiae can trigger Cu detoxification and inactivate Cu uptake systems to protect cells from Cu toxicity (Ballou & Wilson, 2016;Dong, Addinall, Lydall, & Rutherford, 2013). In S. cerevisiae, Cu responsive transcription factor, Ace1, regulates the expression of Cu detoxification-related genes, including those encoding the metallothioneins (MTs) Cup1 and Crs5, and Cu/ Zn SOD1, to adapt to the stress of excess environmental Cu (Beaudoin & Labbe, 2001).…”
Section: Introductionmentioning
confidence: 99%